Comparative Leaf Anatomy under Sun and Shade Conditions and Pollen Morphology of Chrysophyllum rufum Mart. (Sapotaceae) - RÍSIA CEAN S. DE L. SANTOS; CLÁUDIA ELENA CARNEIRO (Anais da Academia Brasileira de Ciências, 2024)
Abstract Chrysophyllum rufum leaves collected under different light conditions provide information on how this fact can influence the morphology of the species. The anatomy techniques applied to the samples showed that there were discreet differences in the characters considered diagnostic. This indicates that the plant is capable of adapting, despite its prevalence in both dry and humid environments. The pollen grains were acetolyzed, measured, described qualitatively, analyzed quantitatively, and illustrated using light microscopy (LM).